Sanskrit Computational Linguistics 4th International Symposium, New Delhi, India, December 10-12, 2010. Proceedings - Jha, Girish Nath.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of the 4th International Symposium on Sanskrit Computational Linguistics, held in New Delhi, India, in December 2010. The 18 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers can be categorized under following broad areas such as phonology and speech technology; morphology and shallow parsing; syntax, semantics and parsing; lexical resources, annotation and search; machine translation and ambiguity resolution.
Rule Interaction, Blocking and Derivation in P??ini -- On the Generalizability of P??ini$1 (Bs Praty?h?ra-Technique to Other Languages -- Building a Prototype Text to Speech for Sanskrit -- Rule-Blocking and Forward-Looking Conditions in the Computational Modelling of P??inian Derivation -- Sanskrit Compound Processor -- Designing a Constraint Based Parser for Sanskrit -- Generative Graph Grammar of Neo-Vai?e?ika Formal Ontology (NVFO) -- Headedness and Modification in Ny?ya Morpho-Syntactic Analysis: Towards a Bracket-Parsing Model -- Citation Matching in Sanskrit Corpora Using Local Alignment -- RDBMS Based Lexical Resource for Indian Heritage: The Case of Mah?bh?rata -- Evaluating Tagsets for Sanskrit -- Performance of a Lexical and POS Tagger for Sanskrit -- The Knowledge Structure in Amarako?a -- Gloss in Sanskrit Wordnet -- Vibhakti Divergence between Sanskrit and Hindi -- Anaphora Resolution Algorithm for Sanskrit -- Linguistic Investigations into Ellipsis in Classical Sanskrit -- Asiddhatva Principle in Computational Model of A???dhy?y? -- Modelling A???dhy?y?: An Approach Based on the Methodology of Ancillary Disciplines (Ved??ga).s
Keywords: Computer science; Software engineering; Computer software; Computational complexity; Artificial intelligence; Translators (Computer programs).; Computer Science; Language Translation and Linguistics; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Discrete Mathematics in Computer Science; Algorithm Analysis and Problem Complexity; Special Purpose and Application-Based Systems